Seni Bertutur sebagai Medium Dialog: Menghubungkan Tradisi dan Inovasi dalam Seni Pertunjukan Kontemporer Indonesia - Fauziah Shahab; I Wayan Adnyana; Ida Ayu Trisnawati; I Gusti Putu Sudarta (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The art of storytelling, as one of Indonesia's rich cultural heritages, plays a crucial role in transmitting the values, norms, and collective identity of society. This study aims to explore the function of the art of storytelling as a medium of dialogue in the context of contemporary performing arts, focusing on how traditional elements can be integrated with modern innovations to create a profound aesthetic experience. Using a qualitative approach, this study analyzes several performances that successfully combine the art of storytelling with contemporary elements, as well as their impact on cultural preservation and strengthening local identity. The results of this study indicate that the art of storytelling functions not only as a means of entertainment but also as a tool for social reflection that can connect different generations. These performances create a space for dialogue that allows audiences to engage emotionally and intellectually, and encourages discussion on relevant issues in society. Thus, this study contributes to the understanding of the importance of the art of storytelling in preserving and celebrating Indonesia's cultural heritage, as well as its role in responding to the challenges of globalization and social change.